Predictors of blunt diaphragm injury in Australia. (January 2023) - Cocco, Annelise M; Ratnaraj, Vignesh; Loveday, Benjamin PT; Gumm, Kellie; Antippa, Phillip; McCormick, Jacob J; Read, David; Thomson, Benjamin
Introduction: Blunt diaphragm injury (BDI) is an uncommon, potentially fatal consequence of blunt torso injury. While associations between BDI and other factors such as mechanism of injury or other injuries have been described elsewhere, little recent research has been done in Australia into BDI. The aims of this study were to determine the incidence rate of BDI in our centre, identify how it was diagnosed, determine rates of missed injury and identify predictive factors for BDI. The hypothesis was that patients with BDI would significantly differ to those without BDI. Methods: All major trauma patients with blunt torso injuries at our Level 1 major trauma service from 2010 to 2018 were included. Data for patient demographics, other injuries, diagnosis and treatment of BDI were extracted. Patients with BDI were compared with patients without BDI in order to identify differences that could be used to predict BDI in future patients. Results: Of 5190 patients with a blunt torso injury, 51 (0.98%) had a BDI at a mean age of 53 ± 19.6 years, and median Injury Severity Score (ISS) of 27(IQR 21–38.5) compared with 5139 patients with a mean age of 48.2 ± 20.7 years and median ISS of 21.9(IQR 14–26) who did not have a BDI. The diagnosis of BDI was made at CT ( n = 35), surgery ( n = 14) or autopsy ( n = 2). Blunt diaphragm injury was missed on index imaging for 11 of 43 patients (25.6%). On multivariate analysis, each point increase in ISS (OR 1.03, p = 0.02); rib fractures (OR 4.65, p = 0.004); splenic injury (OR 2.60, p = 0.004); and liver injury (OR 2.78, p = 0.003) were independently associated with BDI. Conclusion: Injury Severity Score, rib fractures and solid abdominal organ injury increase the likelihood of BDI. In patients with these injuries, BDI should be considered even in the presence of normal CT findings.